Peran Model Kepemimpinan Transformasional Kepala Sekolah dalam Mengimplementasikan Total Quality Management (TQM) untuk Mewujudkan Mutu Berkelanjutan Sekolah Vokasi - Utomo, Widodo Febri; Santosa, Eka Budhi (Jurnal Manajemen Pendidikan, 2024)
Background The role of school principals' transformational leadership becomes crucial. Principals who inspire and empower their staff can drive significant changes in school culture and practices. Purpose This study aims to examine the role of transformational leadership model of school principals in implementing Total Quality Management (TQM) to achieve sustainable quality in vocational schools. Design/method/approach The research method used is a qualitative approach with a case study at one of the vocational schools in Indonesia. Data were collected through in-depth interviews and literature studies. Results The results of the study indicate that the transformational leadership of the school principal serves as a cornerstone in the implementation of TQM. Principals who adopt a transformational leadership style are able to create a clear vision, empower staff, promote a culture of continuous improvement, and manage change effectively. Effective implementation of TQM results in improved quality of learning, student satisfaction, and enhanced operational performance of the school. Contribution/value This study concludes that transformational leadership is a key factor in the successful implementation of TQM to achieve sustainable quality in vocational schools.